Preparation of mesoporous titanosilicate with isolated Ti active centers for cyclohexene oxidation - Gupta, S.; Vinod, C. P.; Jagadeesan, Dinesh (RSC Advances, 2015)
We report the preparation of mesoporous titanosilicate with active Ti centres using CTAB as the structure directing agent and ethylenediamine as the complexing agent (TSC-ED). The finalmaterial contained isolated Ti4+ centres substituting Si4+ in the mesoporous silica framework. The crucial role played by ethylenediamine in complexing with Ti4+ during the sol-gel process and preventing the phase segregation of TiO2 was studied systematically. The textural parameters, structural order, morphology, nature and co-ordination of Ti species were analyzed using various techniques such as X-ray diffraction (XRD), UV-vis diffused reflectance spectroscopy (UV-vis DRS), UV resonance Raman spectroscopy, Fourier transformed Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FESEM), transition electron microscopy (TEM), and X-ray photoelectron spectroscopy. Finally, the catalysts were tested for catalytic activity in the oxidation of cyclohexene using various oxidants.